Distinct N-Linked Immunoglobulin G Glycosylation Patterns Are Associated With Chronic Pathology and Asymptomatic Infections in Human Lymphatic Filariasis - Adjobimey, Tomabu; Hoerauf, Achim (Frontiers in Immunology, 2022)
Lymphatic filariasis presents a complex spectrum of clinical manifestations ranging from asymptomatic microfilariaemic (MF+) to chronic pathology (CP), including lymphedema and elephantiasis. Emerging evidence suggests a link between the physiopathology of filarial infections and antibody properties. Post-translational glycosylation has been shown to play a key role in the modulation of antibodies‘ effector functions. Here, we investigated the link between total IgG-N-glycosylation patterns and the physiopathology of human lymphatic filariasis using UPLC-FLD/ESI-MS comparison of N-glycan profiles of total IgG purified from endemic normals (EN), MF+, and CP patients. We detected a total of 19 glycans released from all IgG samples. Strikingly, agalactosylated glycan residues were more prominent in EN, whereas sialylation and bisecting GlcNac correlated with asymptomatic infections. While IgG from all three clinical groups expressed high levels of fucosylated residues, significantly lower expressions of afucosylated IgG were seen in MF+ individuals compared to EN and CP. Our data reveal distinct N-linked IgG glycan profiles in EN, MF+, and CP and suggest that IgG galactosylation and sialylation are associated with chronic pathology, whereas agalactosylation correlates with putative immunity. The results also indicate a role for sialylation, fucosylation, and bisecting GlcNac in immune tolerance to the parasite. These findings highlight the link between N-glycosylation and the physiopathology of lymphatic filariasis and open new research avenues for next-generation therapeutic formulations against infectious diseases.